IMPLEMENTASI PEMBELAJARAN BERBASIS TEKNOLOGI INFORMASI DAN KOMUNIKASI DENGAN MENGGUNAKAN KOMPUTER MULTIMEDIA DALAM PEMBELAJARAN PAI DI SDIT MUTIARA KOTA PARIAMAN (Jurnal Sosial Humaniora dan Pendidikan, 2022)
The aim of this research is to reveal how Islamic religious education teachers utilize information and communication technology media in the form of computer multimedia in learning. The research method used is descriptive qualitative, research sources consist of events, teachers and several students selected purposively, data is obtained through observation, interviews and documentation studies, the data that has been collected is then analyzed using an interactive approach. The results of the research show that the principal determines ICT-based learning by using multimedia computers in each lesson, PAI teachers carry out ICT-based PAI learning planning using multimedia computers, evaluation of the use of multimedia computers in PAI learning is carried out by PAI teachers themselves to find deficiencies in the implementation of learning. using a multimedia computer.